Pengaruh Perlakuan Alkali-silan terhadap Sifat Mekanis Komposit Hibrid yang Diperkuat Serat Agel dan Serat Gelas : Effect of Alkali-Silane Treatment on Mechanical Properties at Glass Fabric and Woven Agel (Corypha gebanga) Reinforced Hybrid Composites - Hendri Hestiawan; Jamasri; Kusmono (Jurnal Metalurgi dan Material Indonesia, 2020)
The aim of this research is to investigate the effect of alkali-silane on mechanical properties at glass fabric and woven agel (Corypha gebanga) reinforced hybrid composites. The materials used are woven agel fiber, glass fabric, unsaturated polyester resin of yukalac 157 BQTN, and catalyst of methyl ethyl ketone peroxide. Manufacturing techniques used vacuum bagging with a suction pressure of 70 cmHg at room temperature. The woven agel were treated with 4% sodium hydoxide solution for 1 hour, 5% silane solution for 3 hours, and a combined sodium hydoxide and silane solution. The tensile, flexural, and impact test specimens based on ASTM D 638-02, D 790-02, and D 5942-96 standards respectively. The results of tensile, flexural, and impact tests showed that the highest tensile and flexural strength, and impact toughness ​​were obtained on alkali-silane treated hybrid composites, i.e. 78 MPa, 116 MPa, and 38 kJ/m2 respectively. It can be concluded that the alkali-silane treatment effectively improves the mechanical properties of at glass fabric and woven agel reinforced hybrid composites